Profiling the patient with autoimmune hepatitis on calcineurin inhibitors: a real-world-experience. Issue 6 (June 2020) - Pape, Simon; Nevens, Frederik; Verslype, Chris; Mertens, Caroline; Drenth, Joost P.H.; Tjwa, Eric T.T.L.
Abstract : Objective: Therapy for autoimmune hepatitis (AIH) consists of steroid induction therapy, followed by maintenance therapy with azathioprine. However, up to 20% of patients experience either insufficient response or intolerance on first-line therapy. Calcineurin inhibitors (CNIs) are frequently used when first-line therapy fails. Although a number of studies report on efficacy, less is known on the patient trajectory before switch to CNIs. Our aim was to describe the road toward CNI therapy in AIH patients. Methods: Patients with an AIH diagnosis who used CNIs as either second- or third-line treatment were included in the study. Reason for switch to CNI was assessed as either an insufficient response or intolerance to prior therapy. Efficacy was assessed by normalization of transaminases at last moment of follow-up. Results: Final analysis included 20 patients who were treated with CNIs. Ten patients were treated with tacrolimus and ten patients received cyclosporine. In patients who used CNI treatment as third-line therapy (n = 13), duration of first-line therapy was almost twice as long as duration of second-line therapy (2.58 years vs. 1.33 years; P = 0.67). Patients treated with tacrolimus had relatively high trough levels (7.6 ng/mL) and more (minor) adverse events. Fifty-five percent of patients had normalization of transaminases at last moment of follow-up. Conclusion: CNI treatment in AIH as second- or third-line therapy is effective in 50% of patients. The trajectory before switch varies considerably between patients.